Genetic variation and response to selection of photosynthetic and forage characteristics in Kentucky bluegrass (Poa pratensis L.) ecotypes under drought conditions - Shariatipour, Nikwan; Shams, Zahra; Heidari, Bahram; Richards, Christopher (Frontiers in Plant Science, 2023)
Evaluation of the effects of water limited condition on the photosynthetic characteristics and forage yield is important for enhancing the forage productivity and drought tolerance in Kentucky bluegrass (Poa pratensis L.). In the present study, a number of 100 P. pratensis ecotypes collected from different Iran geographical areas were assessed under well-watered and drought stress conditions. Genetic variation and response to selection for the photosynthetic characteristics [i.e. net photosynthesis rate (A), stomatal conductance (gs), transpiration rate (Tr), chlorophyll content (Chl), photochemical efficiency (Fv/Fm)] and forage yield [fresh forage yield (FY), dry forage yield (Dy)] traits were analyzed during 2018 and 2019 growing seasons. Drought stress had negative effects on evaluated photosynthesis parameters and significantly reduced dry and fresh forage yields. On average, FY with 45% decrease and gs with 326% decrease under drought stress condition showed the highest reduction rate among forage yield and photosynthesis traits, respectively. Genotypic coefficients of variation (GCV) for FY were lower under drought stress. The estimates of heritability, genetic advance and genetic advance as percentage of mean showed the predominance of additive gene action for the traits. Overall, the results showed that 'Ciakhor', 'Damavand', 'Karvandan', 'Basmenj', 'Abr2', 'Abrumand', 'Borhan', 'Hezarkanian', 'LasemCheshmeh', 'Torshab' and 'DoSar' showing higher forage yield production with little change between two irrigation conditions regimes, and higher yield can bewhich make them as the promising candidates for developing high-yielding drought tolerant varieties through breeding programs.